Pengaruh Model Pembelajaran Tour Games Turnament (TGT) dengan Media Quizizz Terhadap Hasil Belajar Siswa - Pambudi, Moch. Rio; Eraku, Sunarty Suly (PT. Pubsains Nur Cendekia, 2023)
Learning outcomes are one of the problems that are often encountered in teaching and learning activities. Further analysis shows that this problem has significant implications, especially in the context of social studies classes, especially Geography subjects. Based on the problems described, the most appropriate solution is to implement the Tour Games Tournament model using the Media Quizizz platform. This research aims to determine differences in student learning outcomes with the TGT Media Quizizz learning model at SMAN 1 Suwawa Timur. This research uses a quasi-experimental method with a posttest-only control group design. The research subjects were XI IPS 1 as the experimental class and XI IPS 2 as the control class. There was a significant difference between the experimental group that applied the TGT model with Quizizz media and the control group that used the conventional approach. The results of the hypothesis test were measured at a significance level of 0.001, which was lower than the threshold of 0.05.